SACRAMENTAL ENCOUNTER AMONG RELIGIONS - Pachence, Ronald A (Journal of Dharma, 1981)
Religious pluralism, always accepted as a datum, is now experienced as a value, and students of religion are faced with the task of discovering new ways to reflect upon what happens when living religious traditions meet. The growing body of literature indicates an interest in the endeavour. R. E. Whitson writes as a theologian of the "coming convergence of world religions"; W. C. Smith locates the study of religious traditions in the "faith of other men"; John Dunne advances the concept of "passing over" to share the religious experience of the other; and Charles Davis works in the area of religious symbol and the possibilities of transcultural understanding.